2001
DOI: 10.1159/000048770
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Minichromosome Maintenance 2 (MCM2), Ki-67, and Cell-Cycle-Related Molecules, and Apoptosis in the Normal-Dysplasia-Carcinoma Sequence of the Oral Mucosa

Abstract: Objective: We examined cell cycle and cell death biomarker trends with the normal-dysplasia-carcinoma sequence of the oral epithelia analyzing the pathological significance of a new biomarker, minichromosome maintenance 2 (MCM2). Methods: This study analyzed 12 patients with normal oral epithelia, 69 with dysplasia, and 35 with squamous cell carcinoma (SCC); in 13 patients, SCCs were preceded by dysplasia. The sections were immunostained for MCM2, Ki-67, P53, P27Kip1 and P21CIP1/WAF1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
5
39
0
4
Order By: Relevance
“…The present study showed similar results to that of Kodani et al (2001), although the LIs for Mcm2 and Ki67 were higher in our study. The reason for this might be that Kodani et al quantified cells throughout the whole thickness of the epithelium, from basal to surface epithelial layers.…”
Section: Mcm2 Mcm2supporting
confidence: 89%
See 3 more Smart Citations
“…The present study showed similar results to that of Kodani et al (2001), although the LIs for Mcm2 and Ki67 were higher in our study. The reason for this might be that Kodani et al quantified cells throughout the whole thickness of the epithelium, from basal to surface epithelial layers.…”
Section: Mcm2 Mcm2supporting
confidence: 89%
“…Although these results need to be confirmed by other similar studies, Ki67 and geminin showed no significant difference between the OED groups, however Mcm2 had a marginally but significantly higher mean LI, in the OED that progressed to OSCC than the OED with no history of malignant progression, this was also observed previously (Kodani et al, 2001). These findings could suggest that cells in OED with malignant progression have an increased number of cells licensed to proliferate.…”
Section: Mcm2 Mcm2supporting
confidence: 74%
See 2 more Smart Citations
“…In another study in 2008, Vargas et (Vargas et al, 2008). Studies that have been carried out regarding the cancer of bladder, prostate, breast and oral squamous cell carcinoma have also confirmed the higher expression of MCM2 than Ki-67 (Kodani et al, 2001;Meng et al, 2001;Gonzalez et al, 2003;Korkolopoulou et al, 2005). Szelachowska et al (2006) demonstrated that MCM2 protein predicts better prognosis than Ki-67 in oral cavity squamous cell carcinoma (Szelachowska et al, 2006).…”
Section: Discussionmentioning
confidence: 95%